FACTOR TUBAL AND PERITONIAL DIAGNOSIS AND TREATMENT - Marconi, Guillermo (2015)
Tuboperitoneal factor affects about 25% of the sterile population. During the past 35 years its treatment has been surgical, either by laparoscopy or laparotomy, with acceptable results in term of pregnancies. Surgical success is closely bound to good diagnosis. The use of histerosalpingography and laparoscopy is currently present but none of them show the tube physiomorphology, just its permeability or not. Salpingoscopy is a new element in evaluating tubal epithelium and its ability to act normally. Finally we must emphasize the fact that patients with severe tuboperitoneal factors who failed a surgical attempt or is over 38 years old would not have to waste valuable time and should be directed to a in vitro fertilization program as soon as possible.